ASSESSMENT OF DRUG UTILIZATION AMONG PEDIATRIC PATIENTS IN PRIVATE CLINIC AND PUBLIC HOSPITAL OF BANGLADESH - UDDIN, AHSAN; PAUL, TRIPTI RANI; MONWAR, MONALISA; SARKER, SHAHIN; SULTANA, CHAND; WAHED, MIR IMAM IBNE (International Journal of Pharmacy and Pharmaceutical Sciences, 2020)
Objective: Aim of the study was to assess drug utilization among pediatric patients in both private practice and hospital settings in Rajshahi city, Bangladesh. Methods: This observational study was conducted during a period of two months (March to April) in 2017. Prescriptions were randomly collected from patients and recorded in a predesigned questionnaire form. The data analysis was carried out by using a statistical software package GraphPad Prism. Results: The study involved a total of 185 patients, of which 62.70% were male and 37.30% were female. The patient’s age ranges from 1 mo-12 y and highest number of patients visited physicians belong to group 1 mo-1 y (47.57%). Most commonly occurring disease conditions were pneumonia (24%), the leading cause of hospitalizations among the children's age group of 1 mo-1 y. The results indicated that physician’s handwriting was not clear and legible in 50 (27.03%) prescriptions. A total of 468 drugs were prescribed with an average of 2.53 per prescription. However, none of the drugs were prescribed by generic name. The most commonly prescribed drugs were antibiotics 173 (93.5%). About 78% patients were exposed to antibiotics, of which single antibiotic was prescribed in 116 (62.70%) and two antibiotics in 23 (12.43%) prescriptions. Among the drugs, NSAIDS 65 (35.14%), anti-histamine 57 (30.81%), anti-asthmatic 49 (26.49%) drugs were assigned in prescriptions followed by vitamin and minerals 51 (27.57%). Steroids 57 (30.81%) and hypnotics 26 (14.05%) were also accounted in many prescriptions. Interestingly, antibiotics were indiscriminately prescribed in private practices without any bacteriological examinations, whereas in hospital settings, most of the treatment was initiated after culture and sensitivity tests. Conclusion: Children were highly exposed to antibiotics, steroids and hypnotics in both private practice and hospital settings. So Medical practitioners should be aware of current guidelines for prescriptions of antibiotics and drugs in child.